Plant-Based Milks: Oat - Hannah Cooper; Daniela Rivero-Mendoza; Wendy J. Dahl (EDIS)
Oat milk is one of the more recent dairy alternatives to hit the grocery shelves, and several brands are currently available in the United States. Oat milk is made from the cereal grain oats. This new 3-page publication of the UF/IFAS Food Science and Human Nutrition Department describes how oat milk is made, its ingredients and nutrient profile, and the potential health benefits and risks of consumption. Written by Hannah Cooper, Daniela Rivero-Mendoza, and Wendy J. Dahl. https://edis.ifas.ufl.edu/fs419